Peripheral arterial systolic-diastolic velocities in athletes and non-athletes by doppler ultrasound - Mateus, Sónia (2019)
Intensive sports practice can result in negative consequences. Although the exercise is considered a benefit to the well-being and health of the human being. The form and intensity with which it is practiced can cause negative changes, namely at vascular level, such as changes in the wall and vascular hemodynamic, traumatic injuries, etc. Evaluate the relationship between arterial flow velocities of the lower limbs and the practice of intensive exercise through arterial Doppler ultrasound. Cross-sectional analytical study using arterial Doppler ultrasound of the lower limbs in 76 male subjects, 38 athletes and 38 non-athletes aged 18 to 30 years. The sample was collected over a period of six months in two football clubs in the central region. The mean age was 26 ± 1.8 years for non-athletes and 24 ± 2.79 years for athletes. There is no statistically significant relationship (p = 0.553) between smoking habits and if they are athletes our non-athletes. Regarding the results of the parameters evaluated by Doppler ultrasound the mean of the arterial resistance indices and mean of the systolic and diastolic velocities between the athletes and non-athletes, there were significant variations in some arteries. In this studied sample there is a greater predisposition for athletes to develop small arterial alterations of the lower limbs, however, they are not hemodynamic significant.